1963
DOI: 10.1113/jphysiol.1963.sp007165
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological experiments on the release of the sympathetic transmitter

Abstract: (1960) and by Brandon & Rand (1961). These authors used the contractile response of the effector organ as an index ofthe amount of transmitter liberated. Interpretation of their results is, however, difficult because not only are we ignorant of the relation between transmitter liberation and effector response, but, as Vane (1962) has pointed out, many drugs alter non-specifically the tissue response to catechol amines. We have therefore done our experiment by collecting venous blood from the spleen of the cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
36
1

Year Published

1967
1967
1984
1984

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 10 publications
6
36
1
Order By: Relevance
“…In that case, the former mechanism was rendered already ineffective by the blockade of the a-adrenergic receptors. The a-adrenergic blocking agents were shown to raise the output of the sympathetic transmitter in the venous blood from the spleen when the splenic nerves are excited (Blakeley, Brown & Ferry, 1963). By such an action, the infusion of phentolamine which blocks the a-adrenergic receptors might make available more transmitter to activate the nearby /3-adrenergic receptors and consequently might exaggerate the possible vasodilator influence.…”
Section: Discussionmentioning
confidence: 99%
“…In that case, the former mechanism was rendered already ineffective by the blockade of the a-adrenergic receptors. The a-adrenergic blocking agents were shown to raise the output of the sympathetic transmitter in the venous blood from the spleen when the splenic nerves are excited (Blakeley, Brown & Ferry, 1963). By such an action, the infusion of phentolamine which blocks the a-adrenergic receptors might make available more transmitter to activate the nearby /3-adrenergic receptors and consequently might exaggerate the possible vasodilator influence.…”
Section: Discussionmentioning
confidence: 99%
“…This fraction is not identical with the total release from the nerves and the 'true' release is not easily determined. To obtain a more valid estimation of the 'true' release from the nerve terminals, attempts have been made to obtain a drug-induced increase of the fraction of NA overflowing into the circulation, for example by inhibition of the enzymatic destruction (Brown, 1965;Folkow et al, 1967), inhibition of the membrane pump (Trendelenburg, 1959;Blakeley, Brown & Ferry, 1963;Kirpekar & Cervoni, 1963;Thoenen, Hurlimann & Haefely, 1964a;Geffen, 1965;Boullin, Costa & Brodie, 1967) or a-adrenoceptor blockade (Brown & Gillespie, 1957;Kirpekar & Cervoni, 1963;Rosell, Kopin & Axelrod, 1963;Thoenen, Hiirlimann & Haefely, 1964b;Boullin et al, 1967;Kirpekar & Wakade, 1970). However, great care must be taken when evaluating these results as the drugs used may also change the true release.…”
Section: Introductionmentioning
confidence: 99%
“…This observation confirmed the original finding of Daly & Scott (1961) on the spleen of the dog. Ferry (1963) and Blakeley, Brown & Ferry (1963) concluded that their results suggested a different interpretation of some of the evidence advanced in support of a " cholinergic link " in the post-ganglionic adrenergic sympathetic pathway. More recently Hertting & Widhalm (1965) and Fischer, Weise & Kopin (1966) reported that bretylium blocked the liberation of 3H-noradrenaline produced by electrical stimulation of the splenic nerves at dose levels that did not alter the release of noradrenaline by acetylcholine in the Krebs perfused cat spleen.…”
mentioning
confidence: 98%
“…Ferry (1963) concluded, on the basis of his experimental results, that acetylcholine excited the sympathetic postganglionic nerves of the spleen somewhere near their endings. Blakeley, Brown & Ferry (1963) found that the anticholinesterases eserine and neostigmine did not affect the liberation by the nerves of the sympathetic transmitter. Furthermore, hexamethonium had no effect on the output of noradrenaline produced by electrical stimulation of the splenic nerves, whereas the release of noradrenaline by arterial injection of acetylcholine was prevented by hexamethonium.…”
mentioning
confidence: 99%